Englishpreneurship Program sebagai Upaya Pembelajaran Integeratif di Tingkat Sekolah Dasar - Tri Kristianti; Ar Ruhimat, Imroati Istibsyaroh; Firdaus, Rizalnur (Bahasa Indonesia, 2024)
Continuous and impactful education is considered essential for the creation of the 2045 Golden Generation focused on quality education as one of the main pillars alongside economic equality and development. Educators with integrity and adequate competence in their respective fields and expertise are expected to produce a generation with outstanding potential, and capable of enhancing Indonesia's reputation on the international stage. The mismatch between competencies and the demands of Human Resources (HR) needs can significantly affect the quality of teaching. This Community Service Program is focused on achieving maximum results for students by enhancing the quality of educators to meet the Learning Achievement standards in the Independent Curriculum for English, Entrepreneurship, and Project Creative subjects through a training program titled "Young Learners Entrepreneurship" for elementary school teachers. A qualitative descriptive method is applied using interview techniques, classroom observations, and documentation to obtain primary data so that the program can have the greatest impact and benefit for the selected school partner. Hopefully, this community service's results can improve teachers' competencies and boost their confidence when teaching subjects beyond their expertise. This, in turn, allows the involvement of educational technology applications to continue in future service activities. Abstrak Pendidikan yang berkesinambungan dan berdampak mutlak diperlukan dalam rangka menuju terciptanya Generasi Emas 2045 yang menitikberatkan pada kualitas Pendidikan yang berkualitas ssebagai salah satu pilar utama disamping pemerataan ekonomi dan pembangunanKewirausahaan serta Project kreatif melalui suatu program pelatihan bertajuk Young Learners Entrepreneurship bagi guru Sekolah Dasar. Metode deskriptif kualitatif diaplikasikan dengan menggunakan teknik wawancara, observasi kelas, dan dokumentasi guna mendapatkan data primer agar program tersebut dapat memberikan dampak dan manfaat yang sebesar-besarnya bagi mitra terpilih. Diharapkan hasil dari pengabdian ini dapat bermanfaat untuk meningkatkan kompetensi guru serta meningkatkan rasa percaya diri ketika mengajarkan mata pelajaran diluar bidang kompetensi sehingga keterlibatan teknologi berupa aplikasi endidikan dapat dilanjutkan pada kegiatan pengabdian di masa mendatang.